RESPON PASANGAN USIA SUBUR (PUS) TERHADAP PROGRAM KB GRATIS DI KELURAHAN BUNTU BEDIMBAR KECAMATAN TANJUNG MORAWA KABUPATEN DELI DERDANG - TISSA DWI KARTIKA SARI (Welfare StatE, 2013)
Abstracts Indonesia is one country that has a large population, ie 235 355 196 inhabitants in 2010. While the quality of human resources is still low. To overcome these problems the government making the family planning program (KB), especially a free program that couples KB Fertile Age (EFA) is poor to follow the KB. The family planning program was released since 1951 and continues to grow, so that in 1970 formed the National Family Planning Coordinating Board (BKKBN). This program is one of its aims is to use contraceptive methods pregnancy spacing and creating economic and social welfare for the entire community through the efforts of planning and population control. Type of research is descriptive, where the population numbered 4565 people. In this case the sample is 98 people. The sampling technique used in this study were stratified proportional random sample. The sampling technique is implemented in a state where the population is made ​​up of groups have multilevel arrangement. Data collection techniques used are literature studies and field studies consisting of distributing questionnaires (questionnaires), observations. The data analysis technique used is the qualitative approach, so that later researchers can describe the information and data obtained in the study, in which administration of the data was done manually from the questionnaire data was then tabulated in a frequency distribution and then analyzed. The results of the data analysis is done it can be seen that the Fertile Age Couple Against Urban Planning Program Free Buntu Bedimbar Sub Deli Serdang Regency Tanjung Morawa going well. In this case the program KB Free greatly help ease the burden of considering the condition of the people who grow it every year of high fertility with human resources is still low. Keywords: Response, Fertile Age couple, and KB Free